A wireless sensor network-based monitoring system for freshwater fishpond aquaculture. (August 2018) - Shi, Bing; Sreeram, Victor; Zhao, Dean; Duan, Suolin; Jiang, Jianming
Abstract : Cabled intelligent systems bring with them the complexities of structures, the complications of data measurements and transmission, and a limited scale of application. A wireless sensor network is used to eliminate these disadvantages, however reliability of data transmission and energy saving in a wireless sensor network are two challenges that still need to be addressed. The design information on three types of nodes in a wireless sensor network is described in detail. Tree topology for WSN is adopted to decrease the packet loss rate and improve reliability of data transmission. Allowing sensor nodes to sleep and reorganising the data frames are the two approaches used to achieve energy-saving. The experimental results demonstrate the usefulness of these approaches in solving the challenges. Highlights: This system eliminates the disadvantages of existing cable systems. A favourable topology results in a more reliable system with less packet loss. Energy-saving strategies significantly contribute to the survival of WSN nodes.